Analysis of the spillover characteristics of cooling effect in an urban park: A case study in Zhengzhou city - Gao, Yu; Pan, Huifeng; Tian, Li (Frontiers in Earth Science, 2023)
Urban parks include water bodies, non-hardened ground, and a variety of vegetation, whose shading and evaporation effects form a “park cold island.” A park effectively cools the surrounding environment through heat exchange. This phenomenon is called spillover of park cooling effect (PCS) and plays an important role in regulating the microclimate of cities. Although PCS was extensively documented in previous studies, the effects of park landscape features on PCS still need to be further explored, especially in China with rapid urban expansion. The severe scarcity of urban land resources heightens the necessity to clarify the relationship between park patch size and cooling efficiency. Therefore, in this study, we chose Zhengzhou city (the capital of Henan province, in the central region of China) as an example, which has experienced rapid urban land expansion and urban population and high spatiotemporal aggregation of heatwaves–drought–rainstorms. We used Landsat 8 imagery and high score data in the summer of 2019 to retrieve the characteristics of land surface temperature (LST), and then we extracted 36 city parks and identified the spillover distance of the park cooling effect (PCSD), spillover strength of the park cooling effect (PCSS), spillover rate of the park cooling effect (PCSR), and 11 park landscape indexes. We calculated the area threshold when a park achieves the highest cooling efficiency, and the PCS characteristics of each park also were quantified. The results showed that the average LST of urban parks was 2.3°C lower than that of the entire study area; PCSS was 4.61°C at a maximum; PCSD was between 31 and 370 m, and the average value was 179 m; the average PCSR was 0.957°C/100 m. For the relationship of PCS with the 11 park landscape indexes, we found park area (AREA), park green space area (AREAg), and park perimeter (PERIM) contributed the most to PCS. Shape of impervious surface (LSIi) and percentage of water body (Pw) also significantly contributed to PCS. The ratio of perimeter to area (PARA), edge density (ED), edge density of the green space (EDg), and patch density (PD) were significantly and negatively correlated with PCS. For the relationship between park area and PCS, the result was that the park with an area of 6–8 ha and an internal green area of not less than 5–6 ha has the highest PCS effect. This study can expand our scientific understanding on the influences of park landscape characteristics on PCS and provide a scientific basis for formulating reasonable and effective urban parks and spatial layout planning to cope with the urban heat island effect.